An international multicenter retrospective study to survey the landscape of thrombectomy in the treatment of anterior circulation acute ischemic stroke: outcomes with respect to age. (25th June 2019) - Martini, Michael; Mocco, J; Turk, Aquilla; Siddiqui, Adnan H; Fiorella, David; Hanel, Ricardo; Woodward, Keith; Rai, Ansaar; Frei, Don; Delgado Almandoz, Josser E; Kelly, Michael E; Peeling, Lissa; et al.
Abstract : Background: Thrombectomy is an efficacious treatment for acute ischemic stroke (AIS). However, relatively few studies to date have specifically examined the impact and clinical implications of age on outcomes for thrombectomy in anterior AIS. Objective: To provide a snapshot of patient metrics and outcomes with respect to age following thrombectomy for anterior AIS to supplement the current body of data for predictors of clinical outcomes in a real-world setting. Methods: Data were collected for 20 consecutive patients with AIS treated with thrombectomy at 15 high-volume stroke centers across North America between 2015 and 2016. Patients with anterior occlusions were dichotomized based on whether they were older or younger than 80 years. Ordinal logistic regression analyzed how clinical variables impacted disability using 90-day modified Rankin Scale (mRS) scores. Results: Adequate revascularization (TICI ≥2B) was achieved in 92.3% of patients aged <80 years with an average 1.7±0.1 passes taken with the primary technique and in 88.0% of patients aged ≥80 years with an average 1.7±0.2 passes. Despite similar baseline characteristics, mRS scores were significantly higher in older patients postoperatively and at 90 days after intervention. Age was a significant predictor of 90-day mRS across the study population. Conclusion: This analysis affirms age is a significant determinant of 90-day mRS scores following thrombectomy for large vessel anterior AIS. Further investigation into risks faced by elderly patients during thrombectomy may provide actionable information to help refine patient selection and improve outcomes.